Case report: Dementia sensitivity to altitude changes and effective treatment with hyperbaric air and glutathione precursors - Fogarty, Edward F.; Harch, Paul G. (Frontiers in Neurology, 2024)
A 78-year-old male experienced waxing and waning of dementia symptoms with changes in altitude as he traveled from his home in the Rocky Mountains to lower elevations and back. To replicate the improvement in his symptoms with travel to lower elevations (higher pressure) the patient was treated with a near identical repressurization in a hyperbaric chamber using compressed air. With four one-hour treatments at 1.3 ATA and concurrent administration of lowdose oral glutathione amino acid precursors he recovered speech and improved activities of daily living. Regional broadcast media documented the novel recovery. Nosocomial COVID19 and withdrawal of sustaining hyperbaric therapy led to patient demise seven months after initiation of treatment. It is theorized that hyperbaric air therapy stimulated mitochondrial biochemical and physical changes that led to the clinical improvement.